A Short-Term Altrenogest Treatment Post-weaning Followed by Superovulation Reduces Pregnancy Rates and Embryo Production Efficiency in Multiparous Sows - Gonzalez-Ramiro, Henar; Cuello, Cristina; Cambra, Josep M.; Gonzalez-Plaza, Alejandro; Vazquez, Juan M.; Vazquez, Jose L.; Rodriguez-Martinez, Heriberto; Gil, Maria A.; Lucas-Sanchez, Alejandro; Parrilla, Inmaculada; Martinez, Emilio A. (Frontiers in Veterinary Science, 2021)
Although embryo transfer (ET) is a biotechnology ready for the swine industry, there are factors to be solved, the availability of embryo donors as one. Multiparous sows as donors ought to be considered since weaning is a natural and efficient method for estrus synchronization. In addition, superovulation treatments at weaning are effective in increasing the efficiency of donor embryo production. However, ET programs typically require more donors than those available from a single weaning, imposing grouping several weanings to establish a batch for ET. Since short-term administration of Altrenogest is effective in delaying estrus after weaning without effects on ovulation and embryo development, we investigated how Altrenogest combined with superovulation would affect reproductive parameters and embryo quality and quantity of weaned multiparous donor sows. The sows were administered Altrenogest from the day of weaning for 14 (SS-14 group; N=26), 7 (SS-7 group; N=31) and 4 (SS-4 group; N=32) days. The sows were superovulated with eCG 24 h after the last administration of Altrenogest and with hCG at the onset of estrus. Sows not treated with Altrenogest that were superovulated with eCG 24 h postweaning and hCG at the onset of estrus (SC group; N=37) and sows with natural estrus after weaning (C group; N=34) were used as control groups. The percentage of sows showing estrus within 10 days was not affected by the treatment, but the interval from Altrenogest withdrawal to estrus was longer (P< 0.05) in the SS groups than the interval from weaning to estrus in the controls. SS treatments increased (P< 0.05) the percentage of sows with ovarian cysts and the development of polycystic ovaries. The pregnancy and the fertilization rates, and the overall embryo production efficiency were also negatively affected by the SS treatments (P< 0.05). Interestingly, almost 70% of the structures classified as unfertilized oocytes or degenerated embryos in sows from the SS groups were immature oocytes. In conclusion, although superovulation of weaned sows was highly efficient, short-term administration of Altrenogest in combination with superovulation had negative effects on most of the reproductive parameters assessed, particularly affecting the overall efficiency of pregnancy and embryo production.